2017
DOI: 10.1155/2017/4254750
|View full text |Cite
|
Sign up to set email alerts
|

The Immunosignature of Mother/Fetus Couples in Gestational Diabetes Mellitus: Role of HLA-G 14 bp ins/del and PAPP-A A/C Polymorphisms in the Uterine Inflammatory Milieu

Abstract: We enrolled 151 healthy mother/newborn couples and 26 with gestational diabetes mellitus (GDM). HLA-G and PAPP-A plasma levels were measured by ELISA at first and second trimesters, at delivery, and in cord blood. HLA-G 14 bp ins/del and PAPP-A A/C polymorphisms were genotyped. HLA-G del/del and PAPP-A C/C genotypes were more frequent among GDM mothers than controls. We observed a genetic epistasis between the two polymorphisms: the HLA-G del/del and PAPP-A C/C combination was carried by 8% of GDM mothers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…It was noticed that for diagnosis of GDM, HLA-G at cutoff point > 0.7 had 94% sensitivity and 91% specificity with overall accuracy of 93%. In concordance with our findings, Martinetti and colleagues [20] evaluated 151 non-GDM women and 26 pregnant women with GDM. HLA-G plasma levels were measured by ELISA method at first and second trimesters of pregnancy, at delivery, and in cord blood.…”
Section: Discussionsupporting
confidence: 91%
“…It was noticed that for diagnosis of GDM, HLA-G at cutoff point > 0.7 had 94% sensitivity and 91% specificity with overall accuracy of 93%. In concordance with our findings, Martinetti and colleagues [20] evaluated 151 non-GDM women and 26 pregnant women with GDM. HLA-G plasma levels were measured by ELISA method at first and second trimesters of pregnancy, at delivery, and in cord blood.…”
Section: Discussionsupporting
confidence: 91%
“…The authors concluded that their results showed an association between the degree of glucose intolerance and increased levels of serum HLA‐G that is in accordance with the results of Solini et al who studied the association between HLA‐G and obesity 20,42 . Beneventi was among the co‐workers of a later study by Martinetti et al who found that HLA‐G 14 bp del/del genotype was slightly more frequent in GDM mothers (OR = 1.7) and babies born to GDM mothers (OR = 2.1) than in controls 43 …”
Section: Discussionsupporting
confidence: 86%
“…Besides recurrent pregnancy loss the rs7020782 SNP in PAPPA also associates with the risk of gestational diabetes mellitus, risk of developing carotid plaques, and risk for ischemic cerebrovascular disease 3032 . An altered IGF bioactivity may be present in these cases, because of the reduced proteolysis of IGFBPs by PAPP-A, however, none of these studies included examinations of PAPP-A activity.…”
Section: Discussionmentioning
confidence: 99%